A "Climate-Smart" Model for the Optimization of Tidal Salt Marsh Conservation - Mlsna, Ivy. (2018)
Abstract: Tidal salt marsh ecosystems are vital to the health and protection of northeast United States coastlines. This ecosystem is often the buffer between the ocean and shoreline development, and provides many ecosystem services such as water filtration, habitat for commercially harvested species, and recreational enjoyment. Sea level rise is a threat to salt marshes; as water levels rise, salt marshes will either drown in-place or migrate landward. Marsh migration can only occur into upland areas without development, so it is imperative that these areas are conserved to ensure the future persistence of tidal salt marsh. One of the most effective tools for the protection of this resource is the conservation easement. This study offers a new methodology for the prioritization of conservation investments through use of both socio-environmental as well as resiliency metrics, including metrics for marsh migration, to aid in the identification of sites with the highest conservation value.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Sheldon Krimsky.; Committee: Jon Witten.; Keywords: Climate change, and Area planning & development.